STUDI KASUS PENERAPAN PRINSIP UBD PADA PEMBELAJARAN MATEMATIKA KELAS 5B DI SDN SARIREJO SEMARANG - Sinta Ariana Oktaviani; Qoriati Mushafanah; Suwarni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to explore the implementation of the Understanding by Design (UbD)principle in Mathematics learning for fifth-grade students at SDN Sarirejo, Semarang.The research method used is a case study with a qualitative approach. Data werecollected through observations, in depth interviews, and document analysis.Observations were conducted in the classroom during the learning process using theUnderstanding by Design (UbD) principle, interviews were conducted with studentswho received learning with the Understanding by Design UbD principle, anddocument analysis was conducted using documents in classroom learning duringlearning activities using the Understanding by Design UbD principle. The results ofthe study indicate that the implementation of UbD enhances students conceptualunderstanding of Mathematics and encourages active engangement in the learningprocess. Student demonstrated better ability to connect mathematical concept withreal life situations and explain the reasoning behind their answer. These finding areexcepted to serve as a reference for the development of a more effective curriculumand teaching methods in elementary schools especially in Mathematics learning.